ISOLATION OF AQUAPORIN-1 AND BAND 3 FROM HUMAN RED BLOOD CELLS - Novan Agandra Rois, Muhamad
Efforts to combat global warming involve reducing the amount of carbon dioxide in the atmosphere. One approach is to capture carbon dioxide from the air and convert it into bicarbonate (HCO3 ?) dissolved in water. In human red blood cells, the dissolution mechanism of carbon dioxide involves the complex cooperation of aquaporin-1 (AQP1), band 3 (P3), and carbonic anhydrase II (CAII). A model mimicking the red blood cell mechanism for capturing carbon dioxide has not yet been reported. Therefore, a biomatrix model consisting of AQP1, P3, and CAII can be used as a strategy to dissolve CO2. The fundamental step in constructing this biomatrix is the isolation of AQP1 and P3 from human red blood cells. Human red blood cells were separated from human blood stock, characterized by SEM, lysed with lysis bufer, and cleaned with 1 M KI bufer. AQP1 and P3 were isolated from red blood cell membranes devoid of spectrin-ankirin. Under physiological conditions, red blood cells have an average length of 8.53 ?m and a width of 5.75 ?m with a biconcave disc shape stabilized by the spectrin-ankirin cytoskeleton. AQP1 and P3 were identified with sizes of 28 and 100 kDa on red blood cell membranes. KI washing weakened the interaction of spectrin-ankirin with AQP1 and P3, indicated by reduced spectrin (246 kDa) and ankirin-1 (206 kDa) on the membrane. AQP1 and P3 isolates were obtained through anion exchange chromatography, indicated by peaks at NaCl concentrations of 0.1 – 0.4 M. AQP1 and P3 appeared as thin bands in the isolated fractions, suggesting low amounts. Further validation is needed to confirm the presence of AQP1 and P3 in the isolates. Subsequently, the AQP1 and P3 isolates will be reconstructed with the addition of CAII to form a biomatrix. The activity of carbon dioxide dissolution will be tested by pH changes compared to liposomes as a control. Thus, the activity of the biomatrix can demonstrate the rate of carbon dioxide capture and dissolution, which may help reduce atmospheric carbon dioxide levels.